The role of globalisation in improving human development in Malaysia - Nur Syazwani Mazlan,; Farah Yushanis Fadzilah,; Saifuzzaman Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper examines the impact of globalisation on the level of human development in Malaysia. It also investigates the roles of other potential determinants of human development such as foreign direct investment (FDI), trade openness and international migration on Human Development Index (HDI) in Malaysia. We employ the method of Auto-Regressive Distributed Lag (ARDL) on the annual time series data covering the period from 1980 to 2017. The results confirm a positive and significant long run relationship between globalisation and FDI with HDI in Malaysia. However, the results imply a negative short and long run relationship of both trade openness and international migration with HDI. Therefore, the results suggest for policies to be focused and geared towards fostering globalisation and attracting the inflows of FDI if the country’s main agenda is to improve the level of human development.